Health education on the utilization of pumpkin-based products to lower blood pressure - Apriyani, Apriyani; Wati, Desi Sahlima; Pramesti, Devi Aprilia; Firdaus, Firdaus; Anggraeni, Putri; Adelia, Putri Arsy; Quraisin, Quraisin; Ananda, Qurnia; Susanti, Sherly; Agustina, Silvia; Maryati, Sri (Nur Science Institute, 2025)
Hypertension is a health problem with high prevalence and risk of causing cardiovascular complications. Pumpkin (Cucurbita moschata), rich in potassium and fiber, has the potential to be a non-pharmacological alternative to lower blood pressure. Objective: To increase public knowledge about hypertension and the use of pumpkin as a healthy food. Method: The community service was carried out on February 27, 2025, in Lorong Langgar RT 007/RW 002, 16 Ulu Village, Palembang, attended by 22 residents with hypertension, with the assistance of 10 nursing students. Activities included lectures, discussions, questions and answers, distribution of leaflets, and practice of making gabin bread from pumpkin. Evaluation was carried out with a pre-test and a post-test. Results: Participants' understanding increased significantly from 40% to 80% (average score of 6.5 increased to 12.6). Participants' enthusiasm was high during the discussion and practice. Conclusion: Health education through a combination of lectures, discussions, and pumpkin processing practices effectively increases public understanding of hypertension and its prevention, and can be developed as a promotive-preventive strategy in the community.